2012
DOI: 10.2134/agronj2011.0242
|View full text |Cite
|
Sign up to set email alerts
|

Dryland and Irrigated Corn Yield with Climate, Management, and Hybrid Changes from 1939 through 2009

Abstract: Corn (Zea mays L.) yield has increased from about 1.5 Mg ha−1 in the early 1900s to 8.5 Mg ha−1 in the beginning of the 2000s in the United States. Information about yield and management changes in irrigated and dryland corn yields for the hybrid era is scarce. The objective of the present study was to determine the magnitude of yield and management changes in irrigated and dryland corn from 1939 through 2009. Data from selected irrigated and dryland corn performance trials conducted in Kansas from 1939 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 20 publications
4
35
1
Order By: Relevance
“…8) are in agreement with previous findings (Assefa and Staggenborg, 2010;Assefa et al, 2012;Schlegel et al, 2016bSchlegel et al, , 2017. The results are also in line with previous findings of Stone et al (1996) and Assefa et al (2014) who concluded grain sorghum yields are greater than corn yields with less than 500 mm of total water available for crop use and corn yields are greater than sorghum yields when total available water supply is above 500 mm.…”
Section: Yield As a Function Of Available Soil Water At Planting Andsupporting
confidence: 92%
“…8) are in agreement with previous findings (Assefa and Staggenborg, 2010;Assefa et al, 2012;Schlegel et al, 2016bSchlegel et al, , 2017. The results are also in line with previous findings of Stone et al (1996) and Assefa et al (2014) who concluded grain sorghum yields are greater than corn yields with less than 500 mm of total water available for crop use and corn yields are greater than sorghum yields when total available water supply is above 500 mm.…”
Section: Yield As a Function Of Available Soil Water At Planting Andsupporting
confidence: 92%
“…Maize grain yield increased from about 1,500 kg/ha in the early 1900s to 8,500 kg/ha at the beginning of the 2000s in the USA (Boomsma et al 2009;Assefa et al 2012). Despite this spectacular achievement, maize grain yield is closely related to plant population density (Van Roekel and Coulter 2011), and the crop suffers from an agronomic weakness of prime significance, affecting its grain productivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, optimal plant density should be decided based on detailed G ´ E analysis of production conditions that include factors such as CRM, yield productivity environment (weather-soil ´ management practices), and site information. Assefa et al, 2012;Vyn, 2012, 2014) and increase in the number of plants per unit area is suggested as one of the main contributors to yield improvement (Tokatlidis and Koutroubas, 2004;Duvick, 1997;Carlone and Russell, 1987;Tollenaar and Wu, 1999;Ciampitti and Vyn, 2012). Many of these authors claimed increased tolerance to stress (competition) and responsiveness to inputs achieved through breeding as the main reason for increase in plant density.…”
mentioning
confidence: 99%